Making a Difference through Effective Instructional Strategies - Nanquil, Luisito (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2019)
This article depicts the challenges of language teachers (and all teachers) in the delivery of the instruction and evaluation of the learning process. The author expressed his own views and perspectives regarding the present situations confronting language teachers and other teachers of different subjects. While technology provides the things we need in the classroom setting, there are considerable impediments teachers are facing. What could be the roles teachers in the academy have to fulfill and execute so that they can assist diverse learners? This paper discusses and explains imperative thoughts and reflections that can serve as a guide or framework for all teachers who need clear insights and sensible directions. The method used by the researcher is simply narration-description where he presented his heartfelt and life-relating experiences to the target readers and researchers. To support his claims, he intentionally inserted real-life experiences, observations, and testimonials of teachers and personnel whom he met in his academic journeys. From the thoughts of the author-researcher, it is hoped that readers would be get inspired whenever they fell down and stressed because this essay would remind all who are engaged in teaching that the one of the best professions (if not the best) in the world is being a teacher. Other careers are not possible without the caring and guiding hands of the teachers.